Understanding corporate social responsibility’s influence on brand reputation, employer branding, and performance - Khan,Shaista Kamal (2024)
Abstract Many studies have explored corporate social responsibility (CSR) outcomes in different contexts, but few empirically examine its effects on brand reputation, employer branding, and performance, considering employees' perspectives, particularly in banking. Consequently, this study aims to examine how employees’ perceptions of CSR influence brand reputation, employer branding, and performance in the banking sector, highlighting the mediating role of brand reputation. A quantitative approach was applied using a questionnaire to collect data from employees working in different banks in Pakistan. 254 responses were collected and analysed using PLS-SEM. The findings indicated that CRS positively and significantly impacts brand reputation, employer branding, and performance. Both employer branding and performance are significantly affected by brand reputation, which in turn has a substantial intervening role in the connections between CRS and employer branding and performance. This study contributes to the extant literature on CRS within the banking sector. It provides practical contributions for managers and concerned stakeholders to better understand the consequences of CSR. Limitations and directions for further research are also provided.